Adhesion-induced MoS2 layer transfer via in-situ TEM-nanoindentation: Effects of curvature and substrate mediated residual stress - Jhih H. Liang; Mehdi Rouhani; J. David Schall; Takaaki Sato; Christopher Muratore; Nicholas R. Glavin; Robert W. Carpick; Yeau-Ren Jeng (Applied Surface Science Advances)
Molybdenum disulfide (MoS2) holds great potential in a wide range of applications, including electronics, photodetectors, light-emitting diodes (LEDs), and solar cells due to its unique two-dimensional (2D) structure. This structure enables innovative functionalities, particularly in flexible and wearable technologies. However, a significant knowledge gap remains regarding MoS2's interfacial adhesion, a critical aspect for advancing next-generation devices. To address this, we conducted a comprehensive study investigating the interaction forces originating from the bonding between atoms that govern the adhesion of ultra-thin 2D MoS2. Our pioneering in situ experiments, utilizing TEM-based nanoindentation, provided precise imaging and force monitoring of MoS2's interaction with a diamond. We employed four MoS2-coated AFM tips with varying radii and preparation methods, with films prepared on two Si wafers subjected to different oxidation protocols. Our findings, validated by Raman and X-ray photoelectron spectroscopy, reveal unique insights into MoS2's interfacial behavior. We observed a decreased structural order in MoS2 on sharper tips, particularly those without pre-deposition oxidation. These results underscore the importance of residual stress between the MoS2 film and substrate and the influence of curvature-induced residual stress in fostering less-ordered MoS2 structures with heightened work of adhesion. Importantly, this is the first study to report the work of adhesion for MoS2-diamond contact. Our findings highlight the crucial role of covalent bonding at contact points in the material transfer processes involving 2D materials. This is a critical insight for developing precise and reliable methods for manipulating 2D materials, which could significantly advance our understanding and application of materials science, particularly in nanotechnology and device fabrication.